The effectiveness of cement-palm oil fiber (POF) as soil stabilizer - Nur Atiqah , Zulkifli (2012)
A wide range of reinforcements have been used to improve soil performance to increase the soil strength. Soil stabilization can help in enhancing the soil by improving the soil properties. This research was carried out in order to determine the effectiveness of cement-palm oil fiber (POF) as the soil stabilization. The soil sample was taken at Pekan and the palm oil fiber was taken from a factory located in Lepar Hilir, Gambang, Pahang. The objective of this was to propose the optimum percentage of palm oil fiber to increase the soil engineering characteristics. The tests involved are sieve analysis, Atterberg limit test, standard proctor test, falling head test and unconfined compression test. From the sieve analysis test it is shown that the clay consisted of 24% clay and 76% silt which indicates the soft soil as a silty clay. From the obtained results in Atterberg limit test it is shown that with the presence of 25% palm oil fiber and 5% cement in the mixture it reduced the plasticity index value to 9.67%. Standard proctor test shows the highest value of2l.57kN/m 3 with the mixture of 15% fiber and 85% soft soil. While for the falling head test shows the lowest value for coefficient of permeability which is 5.08 xl 0 7 m/s for the mixture of 75% soft soil, 20% fiber and 5% cement. From the obtained result in unconfined compression test, the mixture of 75% soft soil, 20% fiber and 5% cement brings the highest value of unconfined compressive strength which is 140.67kPa. In overall, it is concluded that the effectiveness of POF can helps the soft soil in enhancing its soil properties and the objectives of this research was achieved.